Lipophilic Statins as Anticancer Agents: Molecular Targeted Actions and Proposal in Advanced Gynaecological Malignancies - Gizzo, Salvatore; Quaranta, Michela; Nardelli, Giovanni B.; Noventa, Marco (Current Drug Targets, 2015)
Despite adequate surgery, women affected by advanced-stage gynaecological cancers (ovarian/ endometrial malignancies) carry an extremely poor prognosis; an improved oncological prognosis could largely depend upon the enhancement of adjuvant treatment. Recent data showed that, among women affected by endometrial/ovarian malignancies, a reduced cancer-related mortality was noted in statin-users compared to non-users, suggesting the need for clinical trials to define the anticancerproperties of statins. In vitro/in vivo evidences suggest a potential chemo-preventive effect through induction of cancer-cell apoptosis and inhibition of cancer-cell growth, proliferation, invasion, and metastasis. The potential oncological impact of this discovery compels us to investigate all possible molecular targets for anticancer activities of statins in order to identify a rationale in proposing their administration in association with standard chemotherapy/radiotherapy protocols after adequate surgical-treatment for advanced-stages gynaecological malignancies.
Keywords: advanced stages of cancer